Penerapan Kegiatan Bermain Uno Stacko Untuk Menstimulasi Kemampuan Regulasi Emosi Anak Usia 5-6 Tahun di TK Qur’an Savaty - Raihanah Mardatillah; Herman Herman; Muhammad Yusri Bachtiar (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The Implementation of Uno Stacko Play Activities to Stimulate the Emotional Regulation Ability of Children Aged 5–6 Years at TK Qur'an Savaty. Undergraduate Thesis. Early Childhood Teacher Education Study Program, Faculty of Education. This study aimed to describe the implementation of Uno Stacko play activities in stimulating the emotional regulation ability of children aged 5–6 years at TK Qur'an Savaty. The research employed a descriptive qualitative approach involving the principal, the classroom teacher, and children in Group B1 as the data sources. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the implementation of Uno Stacko play activities during free play successfully stimulated children's emotional regulation ability. This was reflected in three aspects: recognizing emotions, managing emotions, and expressing emotions appropriately. The children were able to recognize feelings of happiness, disappointment, and enthusiasm during play, manage their emotions when facing challenges or losing the game, and express their emotions appropriately by being patient, cooperative, respecting others, and following the rules of the game. The teacher's role as a facilitator through guidance, assistance, and positive reinforcement also supported the development of children's emotional regulation. Therefore, Uno Stacko play activities can serve as an alternative play activity to stimulate the emotional regulation ability of children aged 5–6 years